Business Strategy Analysis of PT. BPT as Information Technology Value Added Distributor - Sudja, Deddy; Do, Anh Dung (The Indonesian Journal of Business Administration, 2013)
PT. BPT is the information technology value added distributor company for full range IBM Hardware and Software products. PT. BPT as part of CTI Group which is established in 2003. Today BPT faces some business issue which how BPT has to anticipate competitive situation and condition while IT market in Indonesia keep growing with high growth rate. Objective of this paper is to do analysis based on literature for recent business issue and research to confirm those analysis. After that, writer propose business strategy including proposed business model  as growth strategy and in order to win the competition by increasing BPT’s competitiveness. Analysis and research are conducted for external environment, industry environment, competitor and internal environment. Internal environment analysis conducted based on business model canvas analysis (Ostrewalder and Pigneur, 2010). Research conducted by interviewed key peoples in internal BPT and CTI Group and also external such as IBM as principal, business partners and end users as stakeholders. Conclusion of those analysis and research are IT demand in Indonesia will remain grow high. It triggers foreign IT Distributors expand in Indonesia. One of them : Avnet become strong competitor for BPT in term of capital, relation with IBM regional & worldwide and also market coverage in Small Medium Business (SMB) / Mid market and Geo market. Proposed business strategy for BPT as part of growth strategy are leverage technical support as one of value proposition in BPT business model, more focus in Mid market and geo market, acquire or create another / own product and go regional. It takes revision of some components in business model and organization structure. Key words :  business strategy, business model, growth strategy